Halal Label and Subjective Norm: Purchase Intention Through Attitude As An Intervening Variable - Kholil, Masrukhan; Kuncoro, Amin (Global Health Science Group, 2023)
The aim of the research is to test halal labels, subjective norms, attitudes towards purchasing intentions. The data used in this research are primary data and secondary data. Primary data was obtained from the results of questionnaires and secondary data was obtained from literature or journals and previous research. The number of samples in this study was 100 people. The research results show that the halal label, subjective norms improve attitudes. halal label, subjective norms increase purchase intention through attitudes as an intervention.